2012
DOI: 10.1099/jmm.0.036483-0
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of carbapenem-resistant clinical Enterobacteriaceae isolates from a teaching hospital in Shanghai, China

Abstract: Carbapenems such as imipenem and meropenem are first-line agents for the treatment of serious nosocomial infections caused by multidrug-resistant clinical isolates of bacteria belonging to the family Enterobacteriaceae. However, resistance to carbapenems has increased dramatically among members of the family Enterobacteriaceae isolated from a teaching hospital in Shanghai, China. In the present study, we investigated the prevalence and molecular characteristics of carbapenemresistant clinical isolates of Enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 24 publications
(24 reference statements)
3
52
0
Order By: Relevance
“…A high prevalence rate of KPC-2 Enterobacteriaceae isolates has been reported in Zhejiang province, China, and sporadic reports have been made in Shanghai City, Jiangsu, and Jiangxi provinces [14][15][16]. In this study, four KPC-2-producing K. pneumoniae isolates with identical origination were detected.…”
Section: Discussionmentioning
confidence: 75%
“…A high prevalence rate of KPC-2 Enterobacteriaceae isolates has been reported in Zhejiang province, China, and sporadic reports have been made in Shanghai City, Jiangsu, and Jiangxi provinces [14][15][16]. In this study, four KPC-2-producing K. pneumoniae isolates with identical origination were detected.…”
Section: Discussionmentioning
confidence: 75%
“…BL+BLI (betalactamase and betalactamase inhibitor ally) are used for ESBL producing isolates, but carbapenems seemed to be the best options to treat patients with ESBL. Unfortunately, emergence of metallo-beta-lactamases restricted the use of carbapenems [2]. In India, the prevalence of MBLs range from 8% to 79% [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Carbapenemases, however, are not the only mechanisms associated with resistance to carbapenems. For example, studies have shown that the combination of ESBL-AmpC hyperproduction with porin loss contributes to carbapenem nonsusceptibility (13,14,20,36,37).…”
mentioning
confidence: 99%